ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN (Studi Empiris pada Perusahaan Sektor Perbankan yang terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Nur'aini, Mutiara Shafa; Rohman, Abdul (Diponegoro Journal of Accounting, 2024)
This research aims to analyze the influence of good corporate governance on financial performance. The independent variable contained in this research is the good corporate governance mechanism which consists of the number of independent board of commissioners, number of board of directors, number of audit committees, institutional ownership, managerial ownership, and company size. The dependent variable in this research is financial performance which is proxied by the capital adequacy ratio (CAR). The population in this research is banking sector companies listed on the Indonesia Stock Exchange in 2021-2023. By using the purposive sampling method and taking samples based on certain criteria, 99 samples were obtained that were suitable for use. This research was conducted using multiple regression analysis methods.The results of this research reveal that the number of independent board of commissioners has a significant positive effect on financial performance. Meanwhile, institutional ownership and company size have a significant negative effect on financial performance. This research also found that the number of board of directors, number of audit committees and managerial ownership did not have a significant effect on financial performance.